2004
DOI: 10.1074/jbc.m312239200
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the Factor IX γ-Carboxyglutamic Acid Domain to the Vitamin K-dependent γ-Glutamyl Carboxylase Active Site Induces an Allosteric Effect That May Ensure Processive Carboxylation and Regulate the Release of Carboxylated Product

Abstract: Propeptides of the vitamin K-dependent proteins bind to an exosite on ␥-glutamyl carboxylase; while they are bound, multiple glutamic acids in the ␥-carboxyglutamic acid (Gla) domain are carboxylated. The role of the propeptides has been studied extensively; however, the role of the Gla domain in substrate binding is less well understood. We used kinetic and fluorescence techniques to investigate the interactions of the carboxylase with a substrate containing the propeptide and Gla domain of factor IX (FIXproG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Not only is the turnover number of purified VKOR higher than that measured in microsomes; it is also Ϸ10-fold higher than that of the ␥-glutamyl carboxylase (18). Given that VKOR and carboxylase are integral membrane proteins, and that in vitro assays are far removed from actual in vivo conditions, which at the present are unknown, the VKOR turnover number appears to be adequate for the vitamin K cycle.…”
Section: Discussionmentioning
confidence: 97%
“…Not only is the turnover number of purified VKOR higher than that measured in microsomes; it is also Ϸ10-fold higher than that of the ␥-glutamyl carboxylase (18). Given that VKOR and carboxylase are integral membrane proteins, and that in vitro assays are far removed from actual in vivo conditions, which at the present are unknown, the VKOR turnover number appears to be adequate for the vitamin K cycle.…”
Section: Discussionmentioning
confidence: 97%
“…As the first binding event it most likely sets the stage for binding of the other substrates. In addition, the turnover rate during carboxylation of peptide substrates depends to a certain extent on the propeptide affinity for the carboxylase (7). For these reasons we felt that the carboxylase-bound propeptide would be a good model for the enzyme vitamin K-dependent protein precursor complex.…”
Section: Discussionmentioning
confidence: 99%
“…The Effect of Substrates on the Dissociation Rate Constants of Propeptides from Carboxylase-In previous studies from this laboratory, the results showed that under catalytic conditions or with FLEEL, the k off for the propeptide of factor IX was slower than when the propeptide was bound to carboxylase in the absence of substrates (6,7). To determine whether this is a general phenomenon, we determined the k off values for the propeptides of protein C and prothrombin as well as that of factor IX in the presence and absence of FLEEL.…”
Section: K D Values Of Various Carboxylase-propeptide Complexes-mentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 It is also reported that the Gla domain of FIX contributes allosterically to the interaction between its PP and GCX. 25 The affinities of PPs for GCX vary among Vit.K-dependent proteins by more than 100-fold, and the PP of FX has the highest affinity to GCX of all, at least in vitro. 26 The inhibition of PZ secretion by mini-constructs having the PP of FX may have been due to the more dominant interaction of the FX-PP with the PP-binding site of GCX over PZ, by competing the binding of the PZ-PP to GCX.…”
Section: Novel Assay To Detect Inefficient Pz Secretionmentioning
confidence: 99%